Influence of age on the febrile response to E. coli and S. typhimurium endotoxins in growing pullets. - Gregorut, F. P.; Baptista, L. C.; Paulim, A. S.; Guerreiro, J. R.; Secato, E. R.; Macari, Marcos [UNESP] (Taylor & Francis, 1992)
1. The effect of bacterial endotoxin injection was studied in growing pullets of different ages. Commercial chicks were divided into 5 groups according to age. Bacterial endotoxins (E. coli and S. typhimurium) were injected intravenously and rectal temperature was measured over a period of 300 min. 2. The results showed no significant effect of age on the febrile response induced by bacterial endotoxins, but a slight tendency towards a reduced fever peak was observed with increasing age. The response latency also increased with age.
Keywords: endotoxin; aging; animal; animal disease; bird disease; chicken; Escherichia coli; fever; injection; microbiology; pathogenicity; pathophysiology; physiology; Salmonella typhimurium; Aging; Animal; Chickens; Endotoxins; Fever; Injections; Poultry Diseases; Support, Non-U.S. Gov't